Pengenalan Pupuk Kompos Untuk Pertumbuhan Tanaman di Bumi Perkemahan H. M. Yasin Limpo Candika, Kabupaten Gowa, Sulawesi Selatan - Herawaty, Herawaty; Mukhlishah, Nurul; Harlina, Harlina; Mahi, Faizah; Muchtar, Andi Asikin (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Compost fertilizer is the result of weathering foliage, straw, reeds, grass, animal manure, municipal garbage and so on. The use of compost is very important because it can be used as one of the planting media needed to provide adequate nutrition to every growing plant. Community service is carried out to utilize science and technology through counseling on the introduction of compost. This activity consists of preparation, socialization activities in the form of delivering material, and discussion or question and answer. The material presented contains knowledge related to compost, the benefits of compost, materials and how to make compost. This activity was attended by 40 members of the Gowa Branch of the Kwartir Scouts which was carried out at the H. M. Yasin Limpo Campground, Pa'bentengan Village, Bajeng District, Gowa Regency, South Sulawesi Province. received excellent response and enthusiasm from counseling participants. This can be seen from the enthusiasm of the participants starting from the provision of material and questions and answers about compost fertilizer and how to make it.